Kemampuan Pemecahan Masalah Matematis terhadap Hasil Belajar Siswa dalam Pembelajaran Matematika: Studi Literatur - Anggini Anggini; Hasanuddin Hasanuddin (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze students’ mathematical problem-solving abilities and their relationship with learning outcomes in mathematics education. The method employed was library research using a qualitative approach through a literature review. The data sources consisted of 16 relevant scientific articles, with 10 primary articles analyzed in depth. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that students’ mathematical problem-solving abilities generally remain at a moderate to low level. Students tend to be able to understand problems but experience difficulties in planning strategies, carrying out solutions, and reviewing their answers. These abilities are influenced by internal factors, such as cognitive style, learning independence, learning interest, and self-confidence, as well as external factors, such as learning models and methods. Furthermore, a significant relationship was found between mathematical problem-solving abilities and students’ learning outcomes, indicating that the higher the problem-solving ability, the higher the learning outcomes achieved. Therefore, innovative and student-centered learning is needed to improve students’ mathematical problem-solving abilities, which can consequently have a positive impact on their learning outcomes.